1996
DOI: 10.1177/026461969601400206
|View full text |Cite
|
Sign up to set email alerts
|

Types of supportive intervention sought by visually impaired graduates to assist their transition from education to employment

Abstract: This was one of several papers given at the RNIB Seminar on The Disability Discrimination Act and Education held at the University of the West of England, Bristol in November 1995. In this study 51 visually impaired graduates were interviewed on issues relating to their studies and the transition from higher education and post- graduation to employment. The study found that 55% of graduates were in employment and that this figure included only a very few who were under-employed. No link was found between the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…There is also evidence that age, the degree of disability (amount of usable vision), the level of education, gender, and the presence of other disabling conditions have an affect on the rate of employment among working-age persons with visual impairments (Crudden, 2002;Hagemoser, 1996;Hill, 1989;Leonard et al, 1999;Roy, et al, 1996;Tillsley, 1997;Wolffe et al, 1992). Age has been found to have a negative affect on rates of employment (Crudden, 2002), as have being a woman and having other disabling conditions (Leonard et al, 1999), while both the amount of available vision (Hill, 1989;La Grow, 2003;Leonard et al, 1999) and level of education (Hagemoser, 1996;Roy et al, 1996;Wolffe et al, 1992) has been found to have a positive effect. There is mixed evidence on the effect of age at onset on employment rates .…”
Section: Employmentmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also evidence that age, the degree of disability (amount of usable vision), the level of education, gender, and the presence of other disabling conditions have an affect on the rate of employment among working-age persons with visual impairments (Crudden, 2002;Hagemoser, 1996;Hill, 1989;Leonard et al, 1999;Roy, et al, 1996;Tillsley, 1997;Wolffe et al, 1992). Age has been found to have a negative affect on rates of employment (Crudden, 2002), as have being a woman and having other disabling conditions (Leonard et al, 1999), while both the amount of available vision (Hill, 1989;La Grow, 2003;Leonard et al, 1999) and level of education (Hagemoser, 1996;Roy et al, 1996;Wolffe et al, 1992) has been found to have a positive effect. There is mixed evidence on the effect of age at onset on employment rates .…”
Section: Employmentmentioning
confidence: 99%
“…UNDEREMPLOYMENT "Research indicates that not only are persons who have a visual impairment employed at a lower rate, they are also less likely to be employed at levels consistent with their education and skills" (Leonard et al, 1999, p. 33) and are paid less than others and disadvantaged in terms of advancement (Roy et al, 1996). This statement appears to be true in New Zealand as well, where 24% of those who were working said that they worked too few hours, 30% said that the levels of their present jobs were too low for their ability and qualifications, 36% said they thought their chances for advancement were worse than those of their peers, and 40% said that their rates of pay were too low for the jobs in which they were employed (La Grow, 2003).…”
Section: Employmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in the United Kingdom have found more men among visually impaired students (Richardson & Roy, 2002; Roy et al, 1996; Simkiss et al, 1998, p. 46), whereas one survey in the United States found more women (Horn & Berktold, 1999, p. 10). However, Richardson (2010) found that the gender distribution of visually impaired Open University students was not significantly different from that of non-disabled students.…”
Section: Visually Impaired Studentsmentioning
confidence: 94%
“…At a local level, the number of visually impaired students within a single institution may be too small to make reliable comparisons with the attainment of students without disabilities. As a result, researchers have tended to rely on small-scale qualitative studies of the experiences of visually impaired students (e.g., Bishop & Rhind, 2011; Cole-Hamilton & Vale, 2000; Frank, McLinden, & Douglas, 2014; Owen Hutchinson, Atkinson, & Orpwood, 1998; Roy, Dimigen, & Taylor, 1996; Simkiss, Garner, & Dryden, 1998). Such studies provide valuable information that can be used to promote the development of support services, but they do not provide evidence on the more fundamental question of the academic attainment of visually impaired students.…”
Section: The Attainment Of Visually Impaired Studentsmentioning
confidence: 99%